Inducible and tunable gene expression systems for Pseudomonas putida KT2440 - Chandran Sathesh-Prabu (Nature Portfolio, 2021)
Abstract Inducible and tunable expression systems are essential for the microbial production of biochemicals. Five different carbon source- and substrate-inducible promoter systems were developed and further evaluated in Pseudomonas putida KT2440 by analyzing the expression of green fluorescent protein (GFP) as a reporter protein. These systems can be induced by low-cost compounds such as glucose, 3-hydroxypropionic acid (3HP), levulinic acid (LA), and xylose. 3HP-inducible HpdR/P hpdH  was also efficiently induced by LA. LvaR/P lvaA and XutR/P xutA systems were induced even at low concentrations of LA (0.1 mM) and xylose (0.5 mM), respectively. Glucose-inducible HexR/P zwf1  showed weak GFP expression. These inducer agents can be used as potent starting materials for both cell growth and the production of a wide range of biochemicals. The efficiency of the reported systems was comparable to that of conventional chemical-inducible systems. Hence, the newly investigated promoter systems are highly useful for the expression of target genes in the widely used synthetic biology chassis P. putida KT2440 for industrial and medical applications.